Pembangunan “Ekonomi Kreatif” Guna Meningkatkan Kualitas Sumber Daya Manusia Dan Pengembangan Potensi Desa: Desa Arjosari Wilayah Kecamatan Kalipare Kabupaten Malang - Ninda Rachmawati (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
Creative economic development is expected to make a significant contribution to the medium-term regional development goals of 2017–2021, namely converting regional economic potential into high economic growth that generates decent jobs and reduces poverty, supported by a strong economic structure and economic resilience so that development results can be realized. All citizens and people of Kalipare who have strong governance and corporate governance and make Kalipare attractive, calm, and pleasant may enjoy it. The findings give guidelines for identifying regional potential and utilizing the potential of regional resources in Arjosari Village. Counseling via social media, providing material on how to manage and optimize the region’s potential in order to improve human resources in order to realize the creative economy. Knowing the area’s strengths and shortcomings, utilized to find chances to boost the potential of the creative economy in Arjosari village, with a plan to submit a proposal for support to the Creative Economy Infrastructure Banper through https://banper.kemenparekraf.go.id/.